Job Satisfaction as a Mediator of the Influence of Leader-Member Exchange and Organizational Justice on Organizational Citizenship Behavior - Ratna Mitasari; Budi Eko Soetjipto; Syihabudhin Syihabudhin (Universitas KH. Abdul Chalim Mojokerto, 2025)
Organizational behavior is an interdisciplinary field devoted to understanding and managing employees well. This means that organizational behavior is both research-oriented and application. For this reason, organizational citizenship behavior (OCB) is needed. The purpose of this research is to explain the role of job satisfaction in mediating the influence of leader member exchange and OCB. exchange and organizational justice on organizational citizenship behavior. This research method is This research was conducted at PT Power Telecom. Telecom. The number of research samples was 122 people, which were taken using proportional sampling method. Data collection was carried out questionnaire distribution. Data analysis techniques using path analysis. The results showed that leader member exchange and organizational justice have a positive and significant effect on organizational citizenship behavior. Leader member exchange and organizational justice have a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on organizational citizenship behavior. has a positive and significant effect on organizational citizenship behavior. Mediation test results test results show that job satisfaction cannot mediate the effect of leader member exchange and organizational justice on organizational citizenship behavior.